Age-Related Compensatory Gait Strategies During Induced Perturbations in the Pre-Swing Gait Phase: A Kinematic and Kinetic Analysis - Katarzyna Chodkowska; Michalina Błażkiewicz; Andrzej Mroczkowski; Jacek Wąsik (Applied Sciences)
The response to perturbations in the gait of elderly and young individuals can differ due to various factors, such as age-related changes in sensorimotor function, muscle strength, and balance control. This study aimed to identify and compare compensatory kinematic and kinetic gait strategies in response to sudden treadmill perturbations applied during the Pre-Swing phase in young and older adults. The analysis focused on determining age-related differences in joint behavior and force production under perturbation stress, with implications for fall prevention. Twenty-one young and an equal number of elderly healthy females walked on a treadmill in a virtual environment (GRAIL, Motek). Unexpected perturbations were applied five times. Principal Component Analysis (PCA) and k-means clustering identified three distinct compensatory strategies per limb. Young adults primarily employed Strategies I (42.2%) and II (40%), while older adults most often selected Strategy II (45.5%). Statistical analysis (SPM and Mann-Whitney U test, p = 0.05) showed significant between-group differences in joint angles and torques across the gait cycle. For instance, in Strategy I, young participants had significantly lower ankle plantarflexion angles (p < 0.01) and hip extension torques (p < 0.05) compared to the elderly. Strategy II in older adults showed significantly higher vGRF minimums (p < 0.01) and anterior-posterior GRF peaks (p < 0.001). The elderly adopted strategies compatible with their neuromuscular capacity rather than those minimizing joint load, as observed in the young group. These findings offer novel insights into age-related compensatory mechanisms and highlight the importance of tailored fall-prevention strategies based on biomechanical response patterns.